GENDER-BASED DISPARITIES EAST/WEST: RETHINKING THE BURDEN OF CARE IN THE UNITED STATES AND TAIWAN - Tong, Rosemarie (Bioethics, 2007)
When feminist bioethicists express concerns about health-related gender disparities, they raise considerations about justice and gender that traditional bioethicists have either not raised or raised somewhat weakly. In this article, I first provide a feminist analysis of long-term healthcare by and for women in the United States and women in Taiwan. Next, I make the case that, on average, elderly US and Taiwanese women fare less well in long-term care contexts than do elderly US and Taiwanese men. Finally, I explore some suggested practical remedies to reduce gender disparities in long-term care contexts.